2017
DOI: 10.1039/c7nr06861a
|View full text |Cite
|
Sign up to set email alerts
|

Floating rGO-based black membranes for solar driven sterilization

Abstract: This paper presents a new steam sterilization approach that uses a solar-driven evaporation system at the water/air interface. Compared to the conventional solar autoclave, this new steam sterilization approach via interfacial evaporation requires no complex system design to bear high steam pressure. In such a system, a reduced graphene oxide/polytetrafluoroethylene composite membrane floating at the water/air interface serves as a light-to-heat conversion medium to harvest and convert incident solar light int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 32 publications
0
72
0
Order By: Relevance
“…Prior to this work, access to such temperatures normally necessitated pressurization 31 to achieve boiling-point elevation. The innovative structure developed by Zhang et al 32 achieved temperatures as high as 121 °C without pressurization, but required solar concentration ratios in excess of 20 suns (1 sun = 1000 W m −2 ) to achieve this.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this work, access to such temperatures normally necessitated pressurization 31 to achieve boiling-point elevation. The innovative structure developed by Zhang et al 32 achieved temperatures as high as 121 °C without pressurization, but required solar concentration ratios in excess of 20 suns (1 sun = 1000 W m −2 ) to achieve this.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high steam temperatures and pressurization, previous studies relied on high solar flux indicated by the dotted line in quadrants I and III. 12,15,19,31,33,[49][50][51][52][53][54][55] A few recent studies employed a subsequent superheating stage to boost the steam temperature beyond 100 C in open systems (open symbols in quadrant II). 20,32,48 This work demonstrates that it is possible to generate saturated and pressurized steam with low optical concentration represented by the only filled symbol in quadrant II.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the heat carried by hot water vapor can be recycled for electricity generation via thermoelectric ( Figure a) and thermomechanical effects (Figure 15b), [ 66,83 ] or directly utilized for rapid sterilization. [ 81,150–152 ] Converting downward heat loss into electricity has also been demonstrated through thermoelectric method as shown in Figure 15c, which is achieved by taking the advantage of inherently established temperature difference between hot solar absorber and cool water body. [ 68,79,85 ]…”
Section: Perspectivesmentioning
confidence: 99%